Should we shoot intolerance of uncertainty for anxiety disorders? Data from the UK and Indonesia - Yuniardi, M. S.; Psikologi, Fakultas (International Journal of Psychosocial Rehabilitation, 2020)
Intolerance of uncertainty (IU) is originally developed to explain GAD. Recently IU has been proposed as a transdiagnostic factor across anxiety disorders (AD) and later on, it has been targeted in a treatment for comorbidity across AD. No evidence has supported the relative contribution of IU compared to the previously prominent risk factors of AD and its model in explaining comorbidity. in addition, none has examined IU’s significant contribution to AD across cultures. This study investigated the correlation of IU to social anxiety (SA) and generalized anxiety disorder (GAD) amongst the UK and Indonesia students. There were 349 UK students and 538 Indonesian students completed the online questionnaires: IUS-12, BFNE, AS-3, SPIN and PSWQ. Regression and interaction analyses were performed. IU, fear of negative evaluation (FNE) and anxiety sensitivity (AS) consistently made contributions to both psychopathologies on both countries. From the UK data, IU was the second largest contributor to SA and the largest in GAD. There were interactions between IU and FNE and AS on SA and their interactions strengthen each other. Interestingly, IU was the smallest contributor amongst Indonesian students, even in predicting GAD, and it had no interaction with the others. This study highlighted the contribution of IU in AD and supported IU as a possible transdiagnostic factor that can be targeted for comorbidity of AD. However, cultural dimensions may contribute to the relative contribution of IU and thus further study in non-western countries is recommended before targeting IU on treatment for AD or its comorbidity.